Physicochemical Characteristics of Ketapang (Terminalia catappa L.) Seed–Fortified Yogurt - Astrilia Damayanti; Zuhriyan Ash Shiddieqy Bahlawan; Ima Winaningsih; Fitri Nur Kayati; Yessy Anna Pratiwi; Kakalia Putri Auralita; Anggun Enjelita; Calista Arsanti Ramadhani; Harsya Grezdipa Pratama; Ayasha Maharani; Muhammad Fadhlan Dzikri (University of Sultan Ageng Tirtayasa, 2026)
Ketapang (Terminalia catappa L.) seeds are rich in protein and unsaturated fatty acids, making them a promising ingredient for fortifying functional dairy products. This study evaluated the effects of Ketapang seed fortification and starter culture concentrations on the physicochemical characteristics of yogurt. Yogurt was prepared with Ketapang seed milk at 0%, 10%, 15%, and 20% (v/v) and starter culture at 5%, 10%, 15%, and 20% (v/v), then stored at 4 ± 1 °C for 24 h to stabilize the gel structure before analysis. Protein, pH, syneresis, viscosity, and total solids were analyzed using standard methods, with data evaluated by two-way ANOVA and Tukey’s test (p < 0.01). Results showed that fortification significantly improved all parameters: protein increased from 5.67% (control) to 8.54% (20% seeds, 20% starter), total solids rose from 2.71% to 5.59%, viscosity increased nearly four-fold from 40.95 to 164.02 mPa·s, pH declined from 4.41 to 3.80, and syneresis decreased from 0.546 g/g to 0.109 g/g. The synergistic interaction between Ketapang proteins and lactic acid bacteria enhanced the composition, gel structure, and water-holding capacity of yogurt, resulting in firmer, more stable, and nutritionally enriched products. These findings highlight Ketapang seeds as a novel fortification material for the development of high-protein functional dairy products. This research supports Sustainable Development Goals (SDGs 2 and 3) and the national Asta Cita mission by optimizing underutilized local resources to enhance public nutrition.